Exploring blockchain technology adoption challenges in the pharmaceutical industry to promote sustainability: A Pythagorean fuzzy approach - Md Zahidul Anam; Soumik Sarkar; A.B.M. Mainul Bari; Abu Reza Md. Towfiqul Islam; Asif Raihan (Next Sustainability, 2025)
The adoption of blockchain technology holds enormous potential to promote sustainability in the pharmaceutical industry. Blockchain technology can be employed to monitor medicine movements, check drug authenticity, manage patient information, and improve the overall supply chain sustainability performance and data management. However, there are considerable challenges associated with adopting and implementing blockchain technology in the pharmaceutical sector, particularly in an emerging economy like Bangladesh. This study, therefore, aims to develop a framework that identifies and analyzes the challenges in emerging economies using an integrated Multi-Criteria Decision Making (MCDM) approach combining Pythagorean fuzzy theory with the decision-making trial and evaluation laboratory (DEMATEL) method. First, the key challenges were identified from the literature review and expert feedback. Then, the Pythagorean fuzzy DEMATEL (PF-DEMATEL) method was used to assess, rank, and explore the relations among these identified challenges. The obtained results suggest that the most crucial challenges to adopting blockchain technology in the pharmaceutical industry in emerging economies are the complexity to integrate blockchain into the existing system (prominence weight 6.699), data storage and security issues (prominence weight 6.495), and lack of proper IT infrastructure (prominence weight 6.376). Results also indicate that the lack of long-term vision for sustainable implementation (causal weight 1.231) is the most influential, and the lack of universal applicability and proper standardization (causal weight −0.30) is the most influenced challenge. The study's outcome is expected to aid industry managers and policymakers in devising more outcome-based strategies to successfully implement blockchain technology and ensure long-term sustainability in the pharmaceutical sector.